Metabolic Response of Pleurotus ostreatus to Continuous Heat Stress - Yan, Zhiyu; Zhao, Mengran; Wu, Xiangli; Zhang, Jinxia (Frontiers in Microbiology, 2020)
Heat stress seriously threatens the growth of Pleurotus ostreatus. Various studies have been performed to study the resistance of P. ostreatus to heat stress. Here, the metabolome was evaluated to determine the response of P. ostreatus mycelia to heat stress at different times (6, 12, 24, 48 h). More than 70 differential metabolites were detected and enriched in their metabolic pathways. Dynamic metabolites changes in enrichment pathways under heat stress showed that heat stress enhanced the degradation of unsaturated fatty acids and nucleotides, increased the content of amino acids and vitamins, and accelerated glycolysis and the tricarboxylic acid cycle in P. ostreatus. The time course changes of P. ostreatus metabolites under continuous heat stress demonstrated that amino acids continuously changed with heat stress, nucleotides clearly changed with heat stress at 12 h and 48 h, and lipids exhibited an increasing trend with prolonged heat stress, while few types saccharides and vitamins changed under heat stress. Additionally, heat-treated P. ostreatus produced salicylic acid and other stress-resistant substances that were reported in plants. This study first reported the metabolites changes in P. ostreatus mycelia during 48 h of heat stress. The metabolic pathways and substances that changed with heat stress in this research will aid future studies on the resistance of P. ostreatus and other edible fungi to heat stress.